Las canciones infantiles como estrategia para el desarrollo del lenguaje de los niños de preparatoria de la unidad educativa Elvia Bélgica Jiménez, barrio Rumizhitana, parroquia Malacatos. Periodo lectivo 2017-2018 - Ochoa Capa, Leydi Soledad (2019)
The research work entitled: THE CHILDREN'S SONGS AS A STRATEGY FOR THE DEVELOPMENT OF THE LANGUAGE OF PREPARATORY CHILDREN OF THE EDUCATIONAL UNIT "ELVIA BELGIUM JIMÉNEZ", BARRIO RUMIZHITANA, PARISH MALACATOS. LEGAL PERIOD 2017-2018. Its general objective is: To know how children's songs influence as a strategy in the development of the language of high school children of the Educational Unit "Elvia Belgium Jiménez". It is part of a descriptive research. For its development it was necessary to use methods such as: the scientific method, analytical-synthetic, descriptive method and statistical method; In the same way, for obtaining information, techniques were used such as: the teacher's survey to know if the teacher uses children's songs in the daily work, since this has unparalleled potential to improve the children's language development; and as instrumented a checklist applied to 27 children was used, taking as our 15 children to work with the activity guide. From the application of the checklist it is obtained that 11% of the children have difficulty in the pronunciation of fricative phonemes, 56% of the children have difficulty in the articulation of the vibrating and alveolar phonemes, / r /, / rr / After applying the proposal in the post-test, an advance in the articulation was reached with 100% in the fricative phonemes, with 93% in the correct articulation of the vibrating and alveolar phonemes according to the point and way of articulation / r /, / rr /, and the remaining 7% are in the process of acquiring phonemes because these are the last phonemes to be acquired by children. So, it is concluded that the use of children's songs is necessary because they significantly influence the development of language because when applied frequently the child will improve the articulation and pronunciation of the phonemes, finally it is recommended that the teacher design and plan with anticipation activities related to children's songs that stimulates the articulation of phonemes in children.